Cover Image, Volume 20, Issue 1. Issue 1 (7th December 2017) - Loo, Larry Sai Weng; Lau, Hwee Hui; Jasmen, Joanita Binte; Lim, Chang Siang; Teo, Adrian Kee Keong
Abstract : The cover image, by Larry Sai Weng Loo et al., is based on the Review Article An arduous journey from human pluripotent stem cells to functional pancreatic β cells, DOI:10.1111/dom.12996 . Abstract : The cover image, by Larry Sai Weng Loo et al., is based on the Review Article An arduous journey from human pluripotent stem cells to functional pancreatic β cells, DOI:10.1111/dom.12996 .